Rotary ultrasonic machining of CFRP composites: a study on power consumption - Cong, W. L.; Pei, Zhijian J.; Deines, Timothy W.; Srivastava, Anil; Riley, L.; Treadwell, C. (My University, 2012)
Carbon fiber reinforced plastic (CFRP) composites are very difficult to machine. A large number of holes need to be drilled in CFRP for many applications. Therefore, so it is important to develop cost-effective drilling processes. CFRP has been drilled by rotary ultrasonic machining (RUM) successfully. The literature has reports about the effects of input variables on output variables (including cutting force, torque, surface roughness, tool wear, and workpiece delamination) in RUM of CFRP. However, there are no reports on power consumption in RUM of CFRP. This paper reports the first study on power consumption in RUM of CFRP. It reports an experimental investigation on effects of input variables (ultrasonic power, tool rotation speed, feedrate, and type of CFRP) on power consumption of each component (including ultrasonic power supply, spindle motor, coolant pump, and air compressor) and the entire RUM system.
Keywords: Carbon fiber reinforced plastic composite; Drilling; Grinding; Power consumption; Rotary ultrasonic machining